Pengaruh Kualitas Pelayanan, Kewajiban Moral, Sanksi Pajak dan Tapping Box pada Kepatuhan Wajib Pajak Hotel - Mitha Pratiwi, Ni Putu; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 26 No 2 (2019), 2019)
The purpose of this study was to determine the effect of service quality, moral obligations, tax sanctions and the application of transaction recording devices (Tapping Box) on hotel taxpayer compliance at the Regional Financial and Asset Management Agency of Gianyar Regency. This research was conducted at all hotels that have been installed by tapping box devices that are spread in Gianyar Regency. The data analysis technique used is multiple linear regression analysis. Based on the results of the study, this study shows that service quality variables, moral obligations, tax sanctions, and the application of transaction recording devices (Tapping Box) have a positive effect on taxpayer compliance in paying hotel taxes at the Regional Financial and Asset Management Agency of Gianyar Regency. This means that the better quality of service, moral obligations, tax sanctions, and the application of transaction recording devices (Tapping Boxes) will encourage taxpayers to fulfill their tax obligations. Keywords : Service quality, moral obligation, tax sanction, tapping box